Prevalence and Clinical Correlation of Decayed, Missing, and Filled Teeth in Elderly Inpatients With Schizophrenia - Yang, Mi; Li, Qiwen; Deng, Chijun; Yao, Gang; Bai, Xue; Tan, Xi; Zhang, Xiangyang (Frontiers in Psychiatry, 2021)
Introduction Schizophrenia is one of the mental diseases that have a profound impact on human health. Patients with schizophrenia have poor oral hygiene, leading to increased risks of systemic diseases such as respiratory infections and a decline in their quality of life. Therefore, the purpose of this study is to assess the oral health status of inpatients with schizophrenia, analyze its related factors, and thus provide scientific evidence for further exploration of corresponding control strategies. Methods A total of 425 inpatients diagnosed of schizophrenia aged over 50 years from 2 psychiatric hospitals (mean age 58.49 ± 5.72 years old) were enrolled. The demographic data were checked on admission. The caries, missing teeth, and fillings were examined by 2 independent dentists. Mini-Mental State Examination (MMSE) and Global Deterioration Scale (GDSRANK) were performed as cognitive tests. Positive And Negative Syndrome Scale (PANSS) and Repeatable Battery for the Assessment of Neuropsychological Status rating scale (RBANS) were used to determine their mental status. Results The average decayed, missing and filled teeth (DMFT) index was 12.99 ± 8.86. A linear regression analysis showed that the DMFT index had a significantly positive relationship with age (p < 0.001) and smoking (p < 0.001) and had a negative relationship with MMSE (p = 0.029). The missing teeth (MT) index had a positive relationship with age (p < 0.001), smoking (p < 0.001) and GDSRANK (p = 0.014) and a negative relationship with MMSE (p = 0.004). Conclusion The oral health of elderly schizophrenic inpatients is poor, which may be related to the cognitive level of patients and affect the quality of life. We should pay more attention to the oral care of schizophrenic patients and increase the investment in their oral specialized treatment.